2021
DOI: 10.15587/2519-4798.2021.238027
|View full text |Cite
|
Sign up to set email alerts
|

The use of ultrasonic densitometry in assessing bone mineral density and determining the 10-year risk of osteoporotic fractures in older women in the family doctor practice

Abstract: Osteoporosis is the fourth most common disease after cardiovascular, cancer and endocrine diseases. With an increase in life expectancy, it becomes one of the main causes of deterioration in health and an increase in mortality. The aim of the study. To identify women with low bone density using ultrasound densitometry and assess the risk of osteoporotic fractures. Materials and methods. The study was based on a survey of 31 women in the Odessa region, the average age of the subjects was 57±9.1 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“… 29 Currently for suspected OP, a combination of tests are used to determine bone density such as FRAX or Q-Fracture. 30 Blundell et al showed that community pharmacies can effectively provide screening for OP in post-menopausal women. The study also showed that participants screened at risk of developing OP and OPe visited their physicians for further assessment and received pharmacological treatment if appropriate.…”
Section: Discussionmentioning
confidence: 99%
“… 29 Currently for suspected OP, a combination of tests are used to determine bone density such as FRAX or Q-Fracture. 30 Blundell et al showed that community pharmacies can effectively provide screening for OP in post-menopausal women. The study also showed that participants screened at risk of developing OP and OPe visited their physicians for further assessment and received pharmacological treatment if appropriate.…”
Section: Discussionmentioning
confidence: 99%